Novel lycopene epsilon cyclase activities in maize revealed through perturbation of carotenoid biosynthesis - Bai, Ling; Kim, Eun‐Ha; DellaPenna, Dean; Brutnell, Thomas P. (The Plant journal : for cell and molecular biology, 2009)
Summary In maize, human selection for yellow endosperm has led to diversification of grain carotenoid content and composition. This variation has remained largely untapped in modern breeding programs that have focused nearly exclusively on yield gains. In this paper, we show that carotenoid accumulation patterns differ in maize embryo and endosperm tissues, and that this tissue‐specific accumulation is largely mediated through differential expression of genes encoding lycopene β‐cyclase and lycopene ε‐cyclase (LcyB and LcyE). In the absence of LCYB function, LCYE produces a number of unusual carotenes, including δ‐carotene, ε‐carotene and lactucaxanthin (ε,ε‐carotene‐3,3′‐diol), in endosperm tissue. A similar carotene cyclization profile is seen when LcyE is introduced into lycopene‐accumulating Escherichia coli cells, suggesting that the carotenoid profile in the endosperm tissue of the lcyB mutant is largely due to the activity of LCYE in the absence of LCYB. Using site‐directed mutagenesis of LcyE, critical amino acids were defined that regulate the product specificity of the enzyme. Finally, we show that several genes encoding enzymes in isoprenoid and carotenoid biosynthesis are probably subject to negative transcriptional regulation, mediated by a carotenoid or a molecule derived from a carotenoid. The implications of these findings with respect to breeding for carotenoid composition in maize grain are discussed.